Intratendinous Ganglion Cyst of the Hand: A Case Report and Review of the Literature. (14th October 2020) - Chalidis, Byron; Kitridis, Dimitrios; Dimitriou, Christos; Givissis, Panagiotis
Abstract : Intratendinous ganglion of the hand is an extremely rare benign tumor, and only few cases have been reported so far in the literature. We present a case with an intratendinous ganglion of the extensor digitorum communis that treated with en bloc resection and subsequent tendon repair. According to the review of the literature and published data, the ganglion is predominantly located at hand extensor tendons (82%), and it is more frequent among females (75%) and shows a high incidence in 5 th and 6 th decades of life (94.5%). Surgical excision with or without side-to-side repair and/or tendon transfer leads to excellent outcome and low potential for recurrence.